2021
DOI: 10.11604/pamj.2021.38.30.27646
|View full text |Cite
|
Sign up to set email alerts
|

A unique association of bifacial weakness, paresthesia and vestibulocochlear neuritis as post COVID 19 manifestation in pregnant women

Abstract: SARS-CoV-2 is an infection due to a novel virus belonging to the coronavirus family. Since December 2019, first human cases of COVID-19 have been identified in Wuhan (China) and rapidly has been progressed to a global pandemic declared by the world health organization (WHO) on March 11 th 2020. The major complication of COVID-19, is pneumonia, but other presentations like cardiovascular and neurological complications have been reported. Herein, we report a first case of pregnant women pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 8 publications
1
60
0
2
Order By: Relevance
“…The documented time-interval, between the SARS-CoV-2 infection and the onset of audio-vestibular symptoms, was maximally a 6-week period. 17 Major findings such as: first author, country of the study, patient's characteristics, type of audiovestibular manifestations, investigations, treatments and outcomes are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The documented time-interval, between the SARS-CoV-2 infection and the onset of audio-vestibular symptoms, was maximally a 6-week period. 17 Major findings such as: first author, country of the study, patient's characteristics, type of audiovestibular manifestations, investigations, treatments and outcomes are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The database search identified 15 case reports or case series (level of evidence 4) for a total of 20 patients with established SARS-CoV-2 infection. 5 19 All patients reported a new-onset of audio-vestibular symptoms. The mean patient age was 42.4 ± 35.1 years, while the male to female ratio was 7:13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After thorough literature review, we found a substantial number of reported cases and case series of Covid-19 infection presented with GBS. Table 1 summarizes demographic, type of relationship with Covid-19, clinical and GBS sub-types, response to specific GBS treatment, and outcome of different GBS cases who presented in concurrent with Covid 19 infection [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ...…”
Section: Discussionmentioning
confidence: 99%
“…Common neurological symptoms of COVID-19 are headache, dizziness, dysgeusia/ageusia, hyposmia/anosmia, seizure, stroke, and encephalopathy [ 2 ]. There have been reported cases of Guillain-Barré Syndrome (GBS) associated with COVID-19 from different parts of the world [[ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ],[ [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ,…”
Section: Introductionmentioning
confidence: 99%